The Effect of Direct Brain Electrical Stimulation on Concentration and the Record of Pistol Shooter - Farnaz Torabi; Zahra Mortazaeedarsara (University of Tehran, 2022)
AbstractConcentration is an important rool in shooting, Some consider the ability to concentrate to be a natural and inherent talent of athletes, while these abilities are not innate and are skills that athletes can acquire through practice and learning.The use of direct brain electrical stimulation is one of the ways to increase the concentration. This study focused on effect of Transcranial direct current stimulation (tDCS) on the concentration and record of 16 to 26 year old pistol shooters in Isfahan was investigated, 30 subjects (consisted of women and gentlemen were present. 15 of them were in experimental group and 15 subjects were selected for control group. Before the beginning of the study, subjects of both groups were subjected to a pretest including a stroop test and a complete shot form 60 arrows with a scatt machine. Then the experimental group went under the influence of tDCS from the T3 and CZ regions for 20 minutes with voltage of 1 mA per day and it continued for 10 sessions. All subjects were subjected to post-test, which was the same as the pre-test after the end of work and 7 days later. Data were analyzed by SPSS . The results showed that Transcranial direct current stimulation had a significant effect on the concentration and the record of the pistol shooters. The results of both descriptive statistics and inferential statistics (P <0.05) indicated that tDCS had a significant effect on concentration and record of pistol shooters and it improved by using tDCS.